Biochemical Screening for in utero Drug Exposure - E. Wright, Tricia (Drug Metabolism Letters, 2015)
Licit and illicit drug use is a common complication of pregnancy. Accurate information on drug use is difficult to obtain for many reasons as women fear self-disclosure or consenting for drug testing due to stigma, guilt, and fear of social and legal harm. As information about drug use is clinically very important, biochemical testing is an important adjunct to careful maternal history. In addition, research studies depend on accurate measures of exposure when reporting risks of a substance. This paper delineates available matrices for and methods of biochemical drug testing in pregnant women and neonates.
Keywords: pregnancy